2013
DOI: 10.1007/s11239-013-0945-5
|View full text |Cite
|
Sign up to set email alerts
|

Resident performed two-point compression ultrasound is inadequate for diagnosis of deep vein thrombosis in the critically III

Abstract: Doppler ultrasonography is a standard in diagnosis of deep vein thrombosis (DVT) but is often delayed. Clinician-performed focused vascular sonography (FVS) has proven to accurately diagnose DVT in the ambulatory and emergency room settings. Whether trained medical residents can perform quality FVS in the critically ill is unknown. Medical residents were trained in a 2-hour module in FVS assessing for complete compressibility of common femoral and popliteal veins. Residents imaged consecutive medical ICU and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments.…”
Section: Resultsmentioning
confidence: 99%
“…While some studies provided longer training, non-radiology physicians trained from 10 min to 2 h demonstrated sensitivity and specificity of nearly 100% in detecting DVT in the femoral veins in adults with point-of-care US [5, 17, 18]. In contrast to other studies, we trained our teams primarily on the image-acquisition aspects of scanning, and less on the diagnosis of DVT, because we plan to have a central adjudication of DVT in our multicenter randomized control trial [46].…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care US provides a rapid and accurate method of diagnosing DVT in adults in the ICU [4, 5]. Compared with consultative ultrasound or venography, point-of-care US has an average sensitivity of 96.1% and specificity of 96.8% in detecting DVT in the proximal lower extremities [6].…”
Section: Introductionmentioning
confidence: 99%
“…All the patients who referred to Imam Reza Hospital in Mashhad, with clinical symptoms and physical findings with suspected deep vein thrombosis, during the years 2013 and 2014 were included in the study. Given the half-percent prevalence of DVT, and according to previous studies done in this area (Abbasi et al, 2012;Caronia et al, 2014;Farahmand, Farnia, Shahriaran, & Khashayar, 2011;Shiver, Lyon, Blaivas, & Adhikari, 2010) estimation of the number of the patients for study during one year was 70 patients. Patients were included in the study, based on the findings from the history and physical examination on arrival at the emergency department with suspected DVT, independent of age, gender, previous history of deep vein thrombosis, and the risk factors underlying possible.…”
Section: Methodsmentioning
confidence: 99%